Inovasi Rocket Stove Sebagai Solusi Pengurangan Limbah Padat Domestik di Kota Palangka Raya - Gusti Iqbal Tawaqal; Yoga Lesmana, Rudy (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Direct waste incineration is frequently adopted by some communities as an immediate solution for waste management; however, this practice contributes air pollution and the release of dioxins. Open burning releases plumes of thick black smoke containing fine particulate matter, carbon monoxide, and other hazardous compounds. There is a pressing need for appropriate technology capable of significantly reducing waste volume at the source, while remaining environmentally safe and economically viable. The rocket stove, renowned for its high combustion efficiency and low emissions, presents potential as a thermal solution for managing non-hazardous combustible waste. This study was conducted by performing a comparative experimental analysis between the rocket stove method and open burning/conventional, utilizing three experimental replications. The results indicated that the average waste reduction effectiveness of the rocket stove was 98.7% with minimal smoke production, whereas open burning achieved 81.3% with very poor emission quality. Furthermore, the rocket stove demonstrated superior supplemental fuel efficiency, requiring only a single fuel addition compared to the three to five additions necessitated by open burning. Consequently, the rocket stove design significantly mitigates air pollution compared to traditional methods( evidenced by the contrast between minimal smoke and thick smoke) rendering it a safer alternative for waste volume management.